2017
DOI: 10.1159/000479939
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Acute Basilar Artery Occlusion in Early Therapeutic Time Window

Abstract: Background: The natural history of basilar artery occlusion (BAO) is devastating, with morbidity rates increasing up to 80%. However, the efficacy of recanalization therapy for BAO has not been established as yet. Objective: We analyzed consecutive cases of BAO treated with mechanical thrombectomy (MT) to evaluate its safety and efficacy and to determine factors associated with the prognosis. Methods: Between October 2011 and September 2016, MT was performed in 34 patients with BAO. MT was performed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
1
13
0
6
Order By: Relevance
“…6 Our findings of good function outcome in 37% of patients and successful reperfusion in 72% are in agreement with more recent EVT series for patients with BAO. [15][16][17][18][19] The authors report a complication rate of 9%, which is in line with that of the BEST trial which reported symptomatic ICH rate of 8% in the intervention arm. 14 We observed that only baseline NIHSS score, pc-ASPECTS, and BATMAN score were significantly associated with good outcome on univariate analysis, and only the baseline pc-ASPECTS and BATMAN score were significant on multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 72%
“…6 Our findings of good function outcome in 37% of patients and successful reperfusion in 72% are in agreement with more recent EVT series for patients with BAO. [15][16][17][18][19] The authors report a complication rate of 9%, which is in line with that of the BEST trial which reported symptomatic ICH rate of 8% in the intervention arm. 14 We observed that only baseline NIHSS score, pc-ASPECTS, and BATMAN score were significantly associated with good outcome on univariate analysis, and only the baseline pc-ASPECTS and BATMAN score were significant on multivariate logistic regression analysis.…”
Section: Discussionsupporting
confidence: 72%
“…In our cohort, it accounted for three-quarter (n = 75/102) of causative LVOs. There is, however, some evidence from non-randomized studies that EVT of both M2 segment of MCA [12] and basilar artery [13,14] occlusions may result in high recanalization rates and good clinical outcomes. Our study demonstrates that considering MT in broader range of LVO cases (M2, A1, A2, BA, P1), could result in treating one more patient out of ten arriving within the treatment time widow (12%).…”
Section: Discussionmentioning
confidence: 99%
“…The 30% overall rate of good outcome (mRS 0-2) at 3 months is similar or better than in previous BAO cohorts treated with IVT or IAT by us [24]and others [5,15] with rates of 21%-33%, and also comparable with many thrombectomy-treated cohorts [6,8,[25][26][27] with rates between 27% and 36%. Conversely, some EVT cohorts have reported higher rates of good outcome of up to 44%-56% [28][29][30][31] These differences may be partly explained by patient selection, treatment chain-related factors or sample sizes. Yoon et al, [30] Baek et al [29] and Kang et al [31] all reported EVT-treated cohorts with lower NIHSS scores and higher prevalence of atrial fibrillation, The changes in outcome trends during the period 1995-2016 are shown in Figure 1 and Table S1.…”
Section: Discussionmentioning
confidence: 99%